Novel Dissection Station for Endolaryngeal Microsurgery and Laser Surgery: Development and Dissection Course Experience. (6th September 2016) - Mattioli, Francesco; Presutti, Livio; Caversaccio, Marco; Bonali, Marco; Anschuetz, Lukas
Abstract : Objective: We aimed to develop and validate an ex vivo dissection station for endolaryngeal surgery suitable for different kinds of laryngeal specimen and any type of operating technique (CO2 laser, cold instruments by endoscopic or microscopic techniques). Study Design: Experimental construction and validation of a highly specialized dissection station. Setting: Laboratory and international dissection course. Methods: We designed a lightweight dissection station made of polycarbonate resin approved for use with a CO2 laser. The cylindrical box hosts an articulated laryngeal support. The laryngoscope is positioned on an articulated arm, which is fixed on the construction's footplate. Validation of the larynx box was performed during an international dissection course on laryngeal surgery held in January 2016. Results: We assessed the suitability of our novel dissection station among specialized laryngologists with a mean experience of 14 years. Feedback from the participants was very positive, with a mean general impression of 9.5 (out of 10 points) and a recommendation score of 9.6 for further use. Its utility in transforming the taught surgical steps into daily practice has been highly recognized, with a score of 9.5. Conclusion: The lightweight and transparent larynx box is suitable for any kind of laryngeal specimen, and any surgical intervention can be taught at reasonable cost. It is safe and suitable for use with CO2 lasers. Validation among experienced surgeons revealed its suitability in the teaching of endolaryngeal microsurgery and laser surgery.